2003
DOI: 10.1210/en.2002-220630
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Hepatic Peroxisome Proliferator-Activated Receptor α Expression: Influence of Pituitary and Gonadal Hormones

Abstract: Peroxisome proliferator-activated receptor (PPAR) alpha is a nuclear receptor that is mainly expressed in tissues with a high degree of fatty acid oxidation such as liver, heart, and skeletal muscle. Unsaturated fatty acids, their derivatives, and fibrates activate PPARalpha. Male rats are more responsive to fibrates than female rats. We therefore wanted to investigate if there is a sex difference in PPARalpha expression. Male rats had higher levels of hepatic PPARalpha mRNA and protein than female rats. Fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 52 publications
7
88
1
Order By: Relevance
“…In particular, on PND 35, the PPARα mRNA level in males was nearly three times higher than that in females. Consequently, the results of present study of the PPARα mRNA expression level in postnatal male and female rats are consistent with the previous study reported by Jalouli et al (2003).…”
Section: Pparα Expression Analysis In the Developing Rat Liversupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, on PND 35, the PPARα mRNA level in males was nearly three times higher than that in females. Consequently, the results of present study of the PPARα mRNA expression level in postnatal male and female rats are consistent with the previous study reported by Jalouli et al (2003).…”
Section: Pparα Expression Analysis In the Developing Rat Liversupporting
confidence: 93%
“…Several studies have reported that, in rats, males are more responsive compared with females to various effects of peroxisome proliferators (Amacher et al, 1997;Gray and de la Iglesia, 1984;Kawashima et al, 1989aKawashima et al, , 1989bSvoboda et al, 1969). In addition, Jalouli et al (2003) reported that hepatic PPARα mRNA and protein levels were higher in males than in females and castration of male and female rats markedly reduced the sex-related difference in hepatic PPARα mRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in fatty acid metabolism are well known, including in the expression of PPAR␣, which has lower basal expression in females (46). The increase in expression of the PPAR target gene Cpt1 in female homozygous livers suggests an adaptation to cyp27A deficiency by specifically increasing hepatic mitochondrial fatty acid oxidation.…”
Section: Effects Of Gendermentioning
confidence: 99%
“…For PPARa, upregulation in rat liver occurs in a tissue-specific manner in response to fasting, glucocorticoids, and testosterone. [57][58][59] Elevated triglycerides, glucocorticoids (dexamethasone), and PPARa ligands themselves (fibrates) also upregulate liver levels of PPARa. 58,60 Moreover, PPARa expression is upregulated by HMG CoA reductase inhibitors (statins) in rat hepatocytes and human umbilical vein endothelial cells (HUVECs).…”
Section: Transcriptional Regulation Of Ppar Expressionmentioning
confidence: 99%
“…58,60 Moreover, PPARa expression is upregulated by HMG CoA reductase inhibitors (statins) in rat hepatocytes and human umbilical vein endothelial cells (HUVECs). 61 Conversely, PPARa is downregulated by growth hormone, 57 hypoxia, 22 and TNF-a. 62 For PPARg, gene expression is increased in numerous cell types by multiple factors, including cytokines (TNF-a, IL-1b, IL-4), 7 statins, 63 butyrate, 24 cross-linking of IgE receptors on mast cells, 36 and the anti-inflammatory flavinoid amentoflavone.…”
Section: Transcriptional Regulation Of Ppar Expressionmentioning
confidence: 99%